Hypoxia Promotes Syndecan-3 Expression in the Tumor Microenvironment - Prieto-Fernández, Endika; Egia-Mendikute, Leire; Bosch, Alexandre; García del Río, Ana; Jimenez-Lasheras, Borja; Antoñana-Vildosola, Asier; Lee, So Young; Palazon, Asis (Frontiers in Immunology, 2020)
The syndecan (Sdc) family is comprised of four members of cell surface molecules (Sdc-1 to 4) with different biological functions. Syndecan-3 (Sdc-3) is known to be mainly expressed in the brain and nervous tissue and plays a key role in development, cell adhesion and migration. Recent studies point to important roles for Sdc-3 in inflammatory disease, but the patterns of expression and significance of Sdc-3 in cancer remains unexplored. Here we show that Sdc-3 expression is upregulated on several cancer types, especially in solid tumors that are known to be hypoxic. TCGA data demonstrated that Sdc-3 expression in the tumor microenvironment (TME) positively correlates with a hypoxia gene signature. To confirm a potential cause-effect, we performed experiments with tumor cell lines showing increased expression upon in vitro exposure to 1% oxygen or dimethyloxalylglycine (DMOG), an inhibitor of prolyl hydroxylases, indicating that Sdc-3 expression is promoted by hypoxia inducible factors (HIFs). HIF-1α was responsible for this upregulation as confirmed by CRISPR-engineered tumor cells. Using single-cell RNA sequencing data of melanoma patients, we show that Sdc-3 is expressed on tumor associated macrophages (TAMs), cancer cells and endothelial cells. Sdc-3 expression positively correlated with a macrophage gene signature across several TCGA cancer types. In vitro experiments demonstrated that hypoxia (1% oxygen) or treatment with IFN-γ stimulate Sdc-3 expression on RAW-264.7 derived macrophages, linking Sdc-3 expression to a proinflammatory response. Sdc-3 expression correlates with a better patient overall survival in hypoxic melanoma tumors.